Simulation and optimisation of a two-stage/two-pass reverse osmosis system for improved removal of chlorophenol from wastewater. (April 2018) - Al-Obaidi, M.A.; Kara-Zaïtri, C.; Mujtaba, I.M.
Highlights: The two-stage/two-pass RO process design for chlorophenol removal is evaluated. The chlorophenol removal is optimised at a realistic recovery rate value of 40%. The chlorophenol rejection is increased by 12.4% compared to the literature. A reduction of about 4% in the total energy consumption is accomplished. Abstract: Reverse osmosis (RO) has become a common method for treating wastewater and removing several harmful organic compounds because of its relative ease of use and reduced costs. Chlorophenol is a toxic compound for humans and can readily be found in the wastewater of a wide range of industries. Previous research in this area of work has already provided promising results in respect of the performance of an individual spiral wound RO process for removing chlorophenol from wastewater, but the associated removal rates have stayed stubbornly low. The literature has so far confirmed that the efficiency of eliminating chlorophenol from wastewater using a pilot-scale of an individual spiral wound RO process is around 83%, compared to 97% for dimethylphenol. This paper explores the potential of an alternative configuration of two-stage/two-pass RO process for improving such low chlorophenol rejection rates via simulation and optimisation. The operational optimisation carried out is enhanced by constraining the total recovery rate to a realistic value by varying the system operating parameters according to the allowable limits of the process. The results indicate that the proposed configuration has the potential to increase the rejection of chlorophenol by 12.4% while achieving 40% total water recovery at an energy consumption of 1.949 kWh/m 3 .